Design of a PEM fuel cell system for residential application - Gencoglu, Muhsin Tunay; Ural, Zehra (Pergamon-Elsevier Science Ltd, 2009)
Fuel cells are energy transformation technologies and they are clean, don't damage to environment, have high efficiency and provide uninterruptible energy generation. Research and development studies about fuel cells have been done increasingly. In the recent years, fuel cell technologies have performed in some sectors such as military, industrial, space, portable, residential, transportation and trading. Uninterruptible energy is becoming necessary because of high standard of living, increasing of energy demand of residence. Therefore, there is a need for the systems which will provide required energy if the fuel cell is unconnected to grid and the systems will operate as reserve system when the fuel cell connect grid. A fuel cell system worked by hydrogen can be used for the need. Otherwise, hydrogen energy utilization at residences is an alternative method especially for supply power demand of stationary or portable devices. In this paper, hydrogen energy and fuel cells were investigated and application areas of fuel cell systems were researched. In addition, design of a fuel cell system was achieved and the components of the system were defined for the residential application which one of the application areas of fuel cell systems. (c) 2008 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
2nd National Solar and Hydrogen Energy Congress -- JUN 12-13, 2008 -- Eskisehir, TURKEY
Keywords: PEM fuel cell; Hydrogen energy; Residential application